Understanding health care workers’ mental health needs: insights from a qualitative study on digital interventions - Anish K. Agarwal; Rachel E. Gonzales; Lauren Southwick; Devon Schroeder; Meghana Sharma; Lisa Bellini; David A. Asch; Nandita Mitra; Mohan Balachandran; Courtney Benjamin Wolk; Emily M. Becker-Haimes; Rachel E. Kishton; et al. (BMC Health Services Research)
Abstract Importance Health care workers (HCWs) face significant mental health challenges when delivering care and over the span of their careers. Despite growing recognition of these issues, barriers such as stigma, structural limitations, and individual obstacles continue to impede progress in supporting HCWs mental health needs. Digital mental health platforms continue to expand in health systems as they offer novel approaches to address these gaps, but more evidence is needed to understand their reception among HCWs. Objective To examine the perceptions of HCWs regarding their mental health, explore barriers and facilitators to accessing mental health care, and assess their experiences with digital mental health interventions within the context of the pandemic. Design A qualitative study using semi-structured interviews with HCWs who participated in a prior randomized controlled trial (RCT) assessing the impact of a digital mental health platform on anxiety and depression. Setting A large, urban, academic health system. Participants A purposive sample of 64 HCWs, including physicians, nurses, technicians, administrative staff, and social workers, was recruited. Participants were selected from the upper and lower quartiles of anxiety and depression scores from the parent RCT to capture a range of mental health symptomatology. Outcomes and measures The study aimed to identify HCWs’ attitudes toward mental health care, barriers to utilizing professional resources, and their experiences with the digital mental health platform at the local institution. A thematic content analysis was used to analyze the interview data. Results Five major themes were identified: (1) the evolving mental health challenges during and after the pandemic, (2) individual barriers to accessing care, such as personal coping strategies and familial responsibilities, (3) structural barriers like workload and limited access to mental health clinicians, (4) experiences with digital mental health interventions, including text message-based assessments, and (5) recommendations for future digital health strategies to improve access and reduce stigma. Conclusion Digital mental health interventions provide a promising avenue to support HCWs by reducing stigma and improving access to mental health resources and clinicians. However, personalized and system-level changes are necessary to address the ongoing mental health challenges faced by the workforce.